Socio-economic deprivation and visual acuity at presentation in exudative age-related macular degeneration. Issue 5 (17th December 2008) - Acharya, N; Lois, N; Townend, J; Zaher, S; Gallagher, M; Gavin, M
Abstract : Aim: To evaluate the influence of socio-economic factors on visual acuity (VA) at presentation in exudative age-related macular degeneration (AMD). Methods: The medical records of all consecutive patients with newly diagnosed exudative AMD examined at the Ophthalmology Departments of Grampian University Hospitals—NHS Trust, Aberdeen, and Gartnavel General Hospital, Glasgow, between July 2004 and June 2005, were reviewed. Demographics, duration of symptoms, VA in study and fellow eye, exudative AMD characteristics, status of fellow eye and patient home address, used to determine the Scottish Index of Multiple Deprivation (SIMD) score, were recorded. The effect of these parameters on VA at presentation was investigated using general linear modelling. Results: Two-hundred and forty patients (median age 79 years) were included in this study; 44 (18.3%) belonged to the lowest 20% SIMD score (most deprived). Age and location and type of the choroidal neovascularisation were statistically significantly associated with VA at presentation (p = 0.003, p<0.001 and p<0.001, respectively). SIMD scores (p = 0.959), area (Glasgow/Aberdeen) (0.247) and VA in the fellow eye (p = 0.056) were not associated with presenting vision. Conclusions: Age, location and type of choroidal neovascularisation, but not socio-economic deprivation, were associated with VA at presentation in exudative AMD.